Management of Expectations and Reality for Employee Performance - Anisa Nurlitasari Randongkir; Veithzal Rivai v; Azis Hakim (CV. Publikasi Indonesia, 2025)
Effective management of expectations between the organization and employees is key to improving individual and overall organizational performance. This article examines various aspects that need to be considered in managing the gap in expectations and realities that have an impact on employee performance. Many factors are material for managing this condition, but in this article we will discuss the most important factors that are very fundamental both from the side of the organization as management and from the individual side of employees must run in harmony so that management can run well, not create new gaps. These factors are aspects of organizational culture including leadership and effective communication, motivation aspects in employees and aspects of the reward system. This paper presents recommendations for organizations in managing the gap between employee expectations and expectations to be the organization's attention in order to maintain stability towards achieving goals. The importance of managing expectations and reality is an important agenda for every organization to